3D Resources for Visually Impaired Students (Global Journal of Human-Social Science, 2023)
This paper analyzes a process of development of three-dimensional didactic resources created and tested with visually impaired students VIS from Brazilian public schools in which involved designers Middle and High School teachers and students in a collaborative way of creation The importance of interaction among the areas of Engineering Design and Education was analyzed as well The central results were the creation or adaptation of effective teaching
Keywords: visual impairment; universal design; teaching and learning; assistive technology; 3d printing; tactile material